The Evaluation of Efficacy of Calcitriol on Bone Mineral Density, Pain and Quality of Life in Postmenopausal Osteoporotic Patients With or Without Depression - Halil Koyuncu; İlknur Aktaş; Ahmet Dinç; İmdat Özkul; Teoman Aydın; Erdal Yücel; Ömer Kocaman; Halime Toros (Galenos Yayinevi, 2003)
The aim of this study was to determine whether depression was affect on bone loss in postmenopausal osteoporotic (PMO) women and response to calcitriol treatment in this patients. Seventy two females (mean age 65 ± 6.9) were included in this study. Out of these patients, 27 (37.5%) had depression, 45 (62.5%) were normal. All cases were evaluated by DXA, Hamilton depression scale, Short Form-36 (SF-36) scale and visual analog scale. In the patients with depression, L1-L4 t-score (-3.29 ± 1.07), femur total t-score (-2.60 ± 1.00) and z-score (-0.97 ± 0.82) were significantly lower than PMO patients without depression (respectively; -2.71 ± 0.83, -1.86 ± 1.16 and -0.50 ± 0.91). Improvement of t- and z- scores in both groups were statistically significant after calcitriol treatment. Improvement of L1-L4 t- and z-scores and femur neck t-score were higher in patients with depression. SF-36 scores (75.9 ± 19.8) were lower in patients with depression than patients without depression (86.5 ± 14.4) (p=0.041). Negative correlations between Hamilton score and L1-L4 z-score (R=-0.432, p=0.024), femur neck t-score (R=-0.528, p=0.005) were found before treatment. Improvement of pain in both groups were similar. In conclusion, postmenopausal bone loss was higher and the response to calcitriol treatment was better in patients with depression.